2018
DOI: 10.3390/ijms19113564
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanomaterials: Synthesis, Biocompatibility, and Cytotoxicity

Abstract: Graphene, graphene oxide, and reduced graphene oxide have been widely considered as promising candidates for industrial and biomedical applications due to their exceptionally high mechanical stiffness and strength, excellent electrical conductivity, high optical transparency, and good biocompatibility. In this article, we reviewed several techniques that are available for the synthesis of graphene-based nanomaterials, and discussed the biocompatibility and toxicity of such nanomaterials upon exposure to mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
288
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(294 citation statements)
references
References 164 publications
(257 reference statements)
4
288
1
1
Order By: Relevance
“…Previous studies have shown that the information obtained on the in vitro and in vivo toxicity of GBMs due to their dimensions and variation in oxidation states is far from complete [60]. The interactions of living cells with GBMs depends on their hydrophilicity, surface chemistry, purity, lateral dimensions, layer number, and dose [61][62][63][64]. These properties vary greatly according to their synthesis eventually to methods of functionalization.…”
Section: Cytotoxicity and Biocompatibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the information obtained on the in vitro and in vivo toxicity of GBMs due to their dimensions and variation in oxidation states is far from complete [60]. The interactions of living cells with GBMs depends on their hydrophilicity, surface chemistry, purity, lateral dimensions, layer number, and dose [61][62][63][64]. These properties vary greatly according to their synthesis eventually to methods of functionalization.…”
Section: Cytotoxicity and Biocompatibilitymentioning
confidence: 99%
“…GBMs can affect cell membranes and damage them with subsequent cytotoxic effects. Cell membranes contain phospholipids, which are composed of a head group based on phosphate and two chains of fatty acids [61]. The head groups are formed by phosphatic acid modified also by small molecules such as glycerol, inositol, ethanolamine, serine, or choline, which give rise to the phospholipid distinctive properties.…”
Section: Cytotoxicity and Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, graphene‐family materials can promote cell adhesion and proliferation of some types of cells, and SF has good biocompatibility and can provide a scaffold for cell growth ,. So, a combination of the two materials can mimic the natural environment for cell culture.…”
Section: Combined Application Of Graphene‐family Materials and Sfmentioning
confidence: 95%
“…Moreover, GNPs possess the typical anti-adhesion property of graphene, because the absence of basal plane functional groups inhibits the cell adhesion over substrate, and there is also a lower potential for cytotoxicity than graphene oxide, because the absence of oxygen-containing functional groups on the basal plane does not generate reactive oxygen species (ROS) which produce oxidative stress [30,31]. However, regarding the biocompatibility and cytotoxicity of graphene-related materials, conflicting results have been reported in the literature because the response of living cells to these nanomaterials depends greatly on their layer number, lateral size, purity, dose, surface chemistry, and hydrophilicity [32][33][34]. Nevertheless, in a previous study, Zanni et al [35] evaluated the nanotoxicology of GNPs using the model system Caenorhabditis elegans, which is an excellent indicator of nanotoxicology that has highlighted no toxic impact on this animal, nor on its vitality and reproduction capability.…”
Section: Introductionmentioning
confidence: 99%